Latihan Pliometrik dalam Meningkatkan Komponen Fisik : A Systematic Review - Susanti, Rini; Sidik, Dikdik Zafar; Hendrayana, Yudi; Wibowo, Ricky (Faculty of Sport and Health Sciences, 2021)
Most achievement sports even require athletes to have the good physical fitness to achieve optimal performance. Some of the most dominant physical components in achievement of competitive sports, especially sports involving muscles, are physical fitness and motor fitness. The purpose of this literature review is to identify, critique, and summarize the available study evidence regarding plyometric training on the component of physical condition. Data sources are taken from PubMed and Scopus. The search data ranges from January 2010 to December 2020. The inclusion criteria were experimental studies designed in randomized controlled trials related to plyometric training on physical fitness. Data extraction includes objectives, methods, samples, interventions, instruments, and research results. The data were synthesized using a systematic review. Search results in the database yielded 521 studies. There were 10 studies that met the inclusion criteria. The results of the review conclude that the plyometric training program can improve the physical fitness component. The most dominant increase in plyometric training was lower extremity explosive strength, namely leg power and sprint running speed. Sprint running which includes even power really needs plyometric training to improve sprint running performance. Plyometric training also improves physical fitness, specific physical abilities, and strength endurance.